Analysis of the Use of E-commerce in Improving Entrepreneurial Business Competitiveness - Muhammad Nur Afiat; Syamsu Rijal (Jurnal Minfo Polgan, 2023)
In the ever-evolving digital age, the use of e-commerce has become one of the key drivers in the development of entrepreneurial businesses. E-commerce refers to business transactions conducted electronically over the internet, including the sale and purchase of products, services, and information. This research aims to analyse the use of e-commerce in improving the competitiveness of entrepreneurial businesses. This research is qualitative in nature. The techniques used to obtain information involve careful observation and meticulous note-taking, followed by analytical procedures such as data reduction, visualisation, and inference. The study results show that the use of e-commerce in entrepreneurial businesses has great potential to improve competitiveness. E-commerce provides global accessibility, operational efficiency, better customer interaction, in-depth data analysis, and the ability to adapt to market changes. With the right strategy, entrepreneurial businesses can leverage these benefits to achieve greater success.